2014
DOI: 10.5539/ijef.v6n7p71
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Foreign Direct Investment on Economic Growth: A Case Study of Turkey 1980–2012

Abstract: This paper employs time series techniques to analyse the effect of foreign direct investment on economic growth in Turkey. The study uses annual data over the period 1980-2012. The gross domestic product (GDP) is the dependent variable and foreign direct investment (FDI), domestic investment (DIN) and trade liberalization (TL) are the explanatory variables. The empirical analysis starts with run ordinary least square (OLS). The result of Augmented Dickey Fuller (ADF) test hence shows that the series are non-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…In the case of Pakistan, there was unidirectional causality from FDI to electricity and GDP to electricity. Aga (2014), analyze the impact of FDI over GDP in Turkey for the period of 1980 to 2012. Results showed no significant relationship and causality.…”
Section: Fdi and Economic Growthmentioning
confidence: 99%
“…In the case of Pakistan, there was unidirectional causality from FDI to electricity and GDP to electricity. Aga (2014), analyze the impact of FDI over GDP in Turkey for the period of 1980 to 2012. Results showed no significant relationship and causality.…”
Section: Fdi and Economic Growthmentioning
confidence: 99%
“…Using Engle-granger 2-step procedure, all the variables have significant impacts on economic growth in the short run except FDI; the pairwise causality test revealed the existence of unidirectional causality between economic growth and FDI while there was unidirectional and bidirectional causality among some of the variables. Acaravci and Ozturk (2012), examined the long-term relationship between FDI, export and economic growth in new EU countries (Bulgaria, the Czech Republic, Estonia, Hungary, Latvia, Lithuania, Poland, Romania, Slovakia and Slovania) between 1994 and 2008. using the ARDL and Granger causality, they found long-term cointegration in the Czech Republic, Slovakia, Poland and Latvia among the three variables and concluded that FDI seemed to be more important in driving economic growth than export in these countries while there is no long term and causality relationship between FDI and economic growth in Turkey between 1980 and 2012 (Aga, 2014). Likewise, Miankel, Thangavelu, and Kalirajan (2009) in their comparative causality analysis among GDP, export and FDI for six countries (India, Pakistan, Malaysia, Thailand, Chile and Mexico) concluded that in south east Asia; it is GDP growth that attracts FDI in India in the long run and GDP growth promotes export growth in Pakistan, while there is a bi-directional relationship between GDP growth and FDI in Thailand.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the last decade, Nigeria has enjoyed increased international capital inflows as one of the highest recipients of capital inflows from the rest of the world. However, capital inflow especially FDI is not seen to have improved the manufacturing sector and economic growth in Nigeria and this calls for serious concern because Nigeria is yet to experience real inclusive economic growth despite these huge domestic and foreign resources (Akinlo, 2004;Okodua, 2009;CBN,2010;Iwayemi, 2012;Umoh, Jacob, and Chuku, 2012;Ugwuegbe, Okore, and Onoh, 2013;Adejumo, 2013;Aga, 2014;Adofu, Taiga, and Tijani, 2015;Mohammed and Mahfuzul, 2016). These results may be products of undervaluation of what constitute capital inflows and this study takes a broader look at the composition or what constitute the capital inflows in terms of its wideness and depth.…”
Section: Introductionmentioning
confidence: 99%
“…According to World Bank (2018) FDI inflows into Africa are affected by low-level competitiveness, trade openness and ease of doing business. FDI in Africa is hauled in by location-specific advantages that are driven by its natural resources (Arısoy, 2012;Aga, 2014). Zurawicki and Habib (2010) and Pelizzo et al (2016) observe that foreign firms face challenges caused by structural weaknesses in host economies, incomplete and unstable institutional frameworks, underdeveloped political and constitutional court systems, corruption and bureaucratic regulations.…”
Section: Literature Reviewmentioning
confidence: 99%